Responsabilidade processual - Soltanovitch, Renata (2006)
Our goal in this paper is to distinguish the malicious abuse of legal process, indicating the possibility of applying both civil proceeding institutes. In specific cases we indicate responsibility checking, as well as the corresponding sanctions. We also insisted on many times comparing the lawyer s procedural liability with the definitions on the subject contained in the Statutes and the Ethics Code and their corresponding consequences. Finally one can observe in this paper the rules indicated by the procedural liability are not always applied as indicated by law, but we believe that when we present an in-depth discussion of this subject we can start a deeper reflection in the sense of preventing procedural chicaneries and collaborate to speed up proceedings with the resulting procedural effectiveness